In Silico Identification of Mimicking Molecules as Defense Inducers Triggering Jasmonic Acid Mediated Immunity against Alternaria Blight Disease in Brassica Species - Pathak, Rajesh K.; Baunthiyal, Mamta; Shukla, Rohit; Pandey, Dinesh; Taj, Gohar; Kumar, Anil (Frontiers in Plant Science, 2017)
Alternaria brassicae and Alternaria brassicicola are two major phytopathogenic fungi which cause Alternaria blight, a recalcitrant disease on Brassica crops throughout the world, which is highly destructive and responsible for significant yield losses. Since no resistant source is available against Alternaria blight, therefore , efforts have been made in the present study to identify defense inducer molecules which can induce Jasmonic acid (JA) mediated defense against the disease. It is believed that JA triggered defense response will prevent necrotrophic mode of colonization of Alternaria brassicae fungus. The jasmonate receptor, COI1 is one of the potential targets for triggering jasmonic acid mediated immunity through interaction with jasmonate signal. In the present study, few mimicking compounds more efficient than naturally occurring jasmonic acid in terms of interaction with COI1 were identified through virtual screening and molecular dynamics simulation studies. A high quality structural model of COI1 was developed using the protein sequence of Brassica rapa . This was followed by virtual screening of 767 analogs of jasmonic acid from ZINC database for interaction with COI1. Two analogs viz. ZINC27640214 and ZINC43772052 showed more binding affinity with COI1 as compared to naturally occurring jasmonic acid. Molecular dynamics simulation of COI1and COI1-jasmonic acid complex, as well as best screened interacting structural analogs of jasmonic acid with COI1 was done for 50 ns to validate the stability of system. It was found that ZINC27640214 possesses efficient, stable, and good cell permeability properties. Based on the obtained results and its physicochemical properties, it is capable of mimicking jasmonic acid signalling and may be used as defense inducers for triggering JA mediated resistance against Alternaria blight, only after further validation through field trials.